Effect of different matrices on probiotic resistance to in vitro simulated gastrointestinal conditions - Casarotti, Sabrina N. [UNESP]; Todorov, Svetoslav D.; Penna, Ana Lúcia B. [UNESP] (Wiley, 2015)
In this study, we evaluated the effect of different matrices (MRS, milk and milk with inulin) on the tolerance of probiotic strains (Lactobacillus acidophilus La-5 and Bifidobacterium animalis subsp. lactis BB-12) to simulated conditions similar to those found in the gastrointestinal tract. Both probiotic strains demonstrated a significantly lower viability after exposure to in vitro gastric and intestinal conditions, and B. animalis subsp. lactis BB-12 showed higher survival during the test compared to L. acidophilus La-5 in all tested matrices. Milk and inulin protected probiotics from in vitro gastrointestinal stress. These results suggest that it is critical to formulate the food matrix to be used as probiotic carrier.
Keywords: Gastrointestinal tract; Inulin; Lactic acid bacteria; Probiotics